Advanced Nanopatterning Using Scanning Probe Technology. (2019) - Talukder, Santanu; Gogoi, Bedanta; Kumar, Praveen; Pratap, Rudra; Maoz, Rivka; Sagiv, Jacob
Abstract: This paper demonstrates two different lithographic techniques for micro/nanofabrication, viz. electrolithography technique driven by electromigration, and constructive lithography driven by anodic oxidation. The principle of electrolithography is based on electric field induced material transport which can be used for drawing patterns having dimensions from a few nanometres to a few hundred micrometres. Here, a thin Cr film is used as a masking layer and a polymer layer beneath it is used as a pattern transfer layer. A negatively biased scanning probe is used to perform electromigration on the metal film. The best resolution achieved with this technique is 9 nm. On the other hand, with the help of constructive lithography, micro/nano patterns are drawn on a highly ordered organosilane monolayer, self-assembled on silicon, using localized chemical reaction induced by an electrically biased tip or a focused e-beam.